Prediction of a small business financial liquidity against the background of the effectiveness of debt recovery - Wiśniewski, Witold (Prognozowanie płynności finansowej małego przedsiębiorstwa na tle skuteczności windykacji wierzytelności, 2011)
Financial liquidity is one of the major categories of a small business economy. Financial liquidity in small enterprises is based almost entirely on its own sources of financing. Therefore, a special role has to be played in the successful recovery of the claim. The paper presents a simple method for the dynamic analysis of small business liquidity, and the tools that enable to assess the effectiveness of debt recovery. The study uses an econometric system of equations describing the mechanisms of interdependent relationships between liquidity and efficiency of debt recovery. The feedbacks between these variables are taken into account. In this article the technology for estimating forecasts of liquidity and efficiency of small business debt recovery is also discussed. This technology takes into account the existing feedback.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 111-123
Keywords: wielowymiarowa analiza porównawcza; prognozowanie; finanse przedsiębiorstwa; multi-dimensional comparative analysis; forecasting; enterprise finance